2011
DOI: 10.1155/2011/658906
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Photosynthetic Behaviors in Kappaphycus alvarezii Infected by Epiphyte

Abstract: Epiphytic filamentous algae (EFA) were noted as a serious problem to reduce the production and quality of K. alvarezii. The morphological studies revealed that the main epiphyte on K. alvarezii was Neosiphonia savatieri in China. Though the harmful effects of EFA on the production of K. alvarezii have been reported, the detailed mechanism of the N. savatieri in limiting the production of K. alvarezii has not been studied yet. The present paper studied the effects of N. savatieri infection on photosynthetic beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…It is proposed that the difference in structure between N. savatieri and K. alvarezii is mainly responsible for this phenomenon. The main axes of N. savatieri are 60-250 μm in diameter, with segment length 0.5-1.0-fold of the diameter, each vegetative segment consists of four pericentral cells and lacks cortical cells (Masuda et al 2001;Pang et al 2011). Therefore, glyphosate can penetrate into the thalli easily and do integral harm to N. savatieri.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is proposed that the difference in structure between N. savatieri and K. alvarezii is mainly responsible for this phenomenon. The main axes of N. savatieri are 60-250 μm in diameter, with segment length 0.5-1.0-fold of the diameter, each vegetative segment consists of four pericentral cells and lacks cortical cells (Masuda et al 2001;Pang et al 2011). Therefore, glyphosate can penetrate into the thalli easily and do integral harm to N. savatieri.…”
Section: Discussionmentioning
confidence: 99%
“…Vairappan et al (2008) found that the dominant epiphyte in these four culture areas was N. apiculata. The occurrence of N. savatieri in Lian Bay, Hainan Province, the main tropical K. alvarezii culture place in China, has resulted in tremendous decrease in biomass production of Kappaphycus since March 2009 (Pang et al 2011). Even now, only a few people continue to farm Kappaphycus since the outbreak of N. savatieri.…”
Section: Introductionmentioning
confidence: 99%
“…All explants selected for the study appeared clean, green, and healthy. The existence of color strains of K. alvarezii with varied pigmentation (green, red, yellow, and brown) has been reported in the literature for decades, with differences in their physiological characteristics including growth performance and photosynthesis reported from laboratory studies (Dawes and Koch 1991;Aguiree-Lipperheide et al 1995;Hurtado et al 2014;Pang et al 2011).…”
Section: Experimental Phasesmentioning
confidence: 99%
“…This decrease is reportedly correlated with drastic environmental changes in areas with low water motion in both of these locations. Morphological studies performed in China revealed that the main epiphyte on K. alvarezii was N. savatieri and reduced photosynthetic activity caused by extensive shading could be one of the primary reasons for the decreased productivity of K. alvarezii infected by N. savatieri (Pang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Goose‐bumps ( Neosiphonia apiculata infestation, arrows) on K . alvarezii (reproduced from Pang et al ., ).…”
Section: Introductionmentioning
confidence: 97%